Recent progress in sustainable fish byproduct utilisation: unveiling fish collagen as a potential wound healing agent - Abdul Aziz Jaziri; Rossita Shapawi; Ruzaidi Azli Mohd Mokhtar; Wan Norhana Md. Noordin; Sukoso; Nurul Huda (Sciendo, 2025)
Utilizing fish byproducts is a strategic focus on reducing waste from fish processing, garnering significant global attention from researchers and fish processors aiming for sustainable practices in line with Sustainable Development Goal 12 by 2030. One highly effective approach involves converting these byproducts into valuable commodities, such as collagen and its hydrolysates. Collagen is an important protein in living organisms that serve as fibrous structural components in the extracellular matrix. For last a decade, fish collagen has gained interest due to its superior physicochemical properties, biocompatibility, biodegradability, safety, and high absorption by the human body. These attributes make fish collagen a promising area of research, particularly for wound healing applications. This review covers the extraction procedures and characteristics of collagen derived from fish byproducts, providing a comprehensive overview of the methods used to obtain high-quality collagen. Additionally, it highlights recent research progress on the use of collagen as a wound healing agent, evaluated through both in vitro and in vivo studies. The review also addresses the challenges associated with applying collagen for wound healing, such as optimizing extraction methods, ensuring consistent quality, and overcoming potential regulatory hurdles. Furthermore, it presents a future perspective on the potential of fish collagen as an efficient and effective wound healing product, emphasizing its role in advancing biomedical research and applications. By offering new insights and stimulating further development in the utilization of fish collagen, this review aims to contribute to waste reduction in fish processing and enhance the economic value of byproducts. Thus, fish collagen holds significant promise as a sustainable and innovative solution in the biomedical field, aligning with global efforts to achieve sustainability and improve human health.